Evaluating the effectiveness of social assistance programs for poverty reduction: Evidence from Baramamase Village, Indonesia - Jewed, Fauziah; Abdullah, Muh. Ruslan; Ishak, Ishak (Universitas Islam Indonesia, 2025)
IntroductionIndonesia continues to face the challenge of multidimensional poverty despite multiple government initiatives. Social assistance programs such as food aid, conditional cash transfers, health insurance subsidies, and direct village fund transfers have been implemented nationwide. However, concerns about mistargeting, weak management, and limited long-term impact persist. This study examines the implementation and effectiveness of social assistance in Baramamase Village to understand how these programs contribute to welfare improvement at the local level.ObjectivesThe study aims to evaluate whether the design and implementation of social assistance programs in the village achieve their intended goals, to identify the factors that influence their effectiveness, and to assess the extent to which they improve household welfare beyond short-term relief.MethodA qualitative descriptive method was employed using observation, interviews with program implementers and beneficiaries, and documentation. Data were analyzed using the Context, Input, Process, and Product (CIPP) framework to capture institutional settings, resources, implementation mechanisms, and welfare outcomes. NVivo software was used to organize and analyze interview data.ResultsThe findings reveal that program effectiveness depends heavily on local governance, accurate data, and active community participation. Health insurance subsidies show the most consistent positive impact on welfare protection and sustainability, while conditional cash transfers improve education and health outcomes for children. Food aid contributes to short-term consumption but offers limited long-term benefits, and village fund cash transfers are valued by recipients but face distributional challenges. Beneficiaries report immediate relief and satisfaction, yet also express concerns about adequacy and continuity.ImplicationsThe results suggest that social assistance plays a vital role in protecting poor households from shocks and ensuring access to basic needs. Nevertheless, its transformative effect on long-term welfare is constrained without complementary empowerment strategies. Policy improvements are needed in data accuracy, transparency, inter-institutional coordination, and the integration of skill-building and livelihood support to reduce dependency.Originality/NoveltyThis study provides a localized and comprehensive assessment of social assistance effectiveness using the CIPP evaluation framework. By highlighting the interplay between management quality, data integrity, and beneficiary participation, it contributes to policy discourse on how to transform social assistance from temporary relief into a sustainable path toward welfare enhancement.